Negative pressure wound therapy use in diabetic foot syndrome—from mechanisms of action to clinical practice. (29th January 2019) - Borys, Sebastian; Hohendorff, Jerzy; Frankfurter, Claudia; Kiec‐Wilk, Beata; Malecki, Maciej T.
Abstract: Background: Diabetes and its complications constitute a rising medical challenge. Special attention should be given to diabetic foot syndrome (DFS) due to its high rate of associated amputation and mortality. Negative pressure wound therapy (NPWT) is a frequently used supportive modality in a diabetic foot with ulcerations (DFUs). Design: Here, we reviewed the current knowledge concerning the tissue and molecular mechanisms of NPWT action with an emphasis on diabetes research followed by a summary of clinical DFU studies and practice guidelines. Results: Negative pressure wound therapy action results in two types of tissue deformations—macrodeformation, such as wound contraction, and microdeformation occurring at microscopic level. Both of them stimulate a wound healing cascade including tissue granulation promotion, vessel proliferation, neoangiogenesis, epithelialization and excess extracellular fluid removal. On the molecular level, NPWT results in an alteration towards more pro‐angiogenic and anti‐inflammatory conditions. It increases expression of several key growth factors, including vascular endothelial growth factor and fibroblast growth factor 2, while expression of inflammatory cytokinesis reduced. The NPWT application also alters the presence and function of matrix metalloproteinases. Clinical studies in DFU patients showed a superiority of NPWT over standard therapy in terms of efficacy outcomes, primarily wound healing and amputation rate, without a rise in adverse events. International guidelines point to NPWT as an important adjuvant therapy in DFU whose use is expected to increase. Conclusions: This current knowledge improves our understanding of NPWT action and its tailoring for application in diabetic patients. It may inform the development of new treatments for DFU.